2021
DOI: 10.34297/ajbsr.2021.11.001675
|View full text |Cite
|
Sign up to set email alerts
|

Association of Vascular Endothelial Growth Factor +405G/C Polymorphism with Diabetic Retinopathy among Sudanese Patients

Abstract: This work is licensed under Creative Commons Attribution 4.0 License AJBSR.MS.ID.001675.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…This study could only find an association of rs13207351 with NPDR and rs5742632 with PDR [107]. Similarly, studies performed in the Caucasian Slovenian and Mexican PDR subjects did not observe an association between AA genotype of rs6921438 or rs10738760 [108,109] and rs3025021, rs3025035, rs2010963, respectively [110]; however, recent studies have also shown that rs2010963 is associated with the development and severity of DR in Egyptian [111] and Sudanese [112] patients.…”
Section: Vegf Genementioning
confidence: 58%
“…This study could only find an association of rs13207351 with NPDR and rs5742632 with PDR [107]. Similarly, studies performed in the Caucasian Slovenian and Mexican PDR subjects did not observe an association between AA genotype of rs6921438 or rs10738760 [108,109] and rs3025021, rs3025035, rs2010963, respectively [110]; however, recent studies have also shown that rs2010963 is associated with the development and severity of DR in Egyptian [111] and Sudanese [112] patients.…”
Section: Vegf Genementioning
confidence: 58%